Republic of Estonia : Staff Report for the 2010 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
Despite enduring one of the sharpest contractions in the EU, Estonia has been successful in its all-out efforts to join the euro area. Core prices have also begun increasing but at a moderate rate. Recent wage increases have defied not only high unemployment but also increases in vacancies and long-term unemployment. Executive Directors welcomed the authorities' medium-term goal of returning to budget surpluses to restore fiscal reserves and keep public debt at low levels. Directors observed that the financial sector had weathered the crisis relatively well.